Rules and regulations of The United Brothers' Birmingham Benefit Society (London : J.S. Forsaith & Son, Printers (T.U.), 1908)
1908 1908 1900s 18 pages RULES & REGULATIONS OF THE UNITED BROTHERS BIRMINGHAM BENEFIT SOCIETY. HELD AT "The Norfolk Arms," Ivimey Street, Barnet Grove Bethnal Green ESTABLISHED 1853. LONDON: J.S. FORSAITH & SON, PRINTERS (T.U.), 329, BETHNAL GREEN ROAD, N.E. 1908 345/7/2/2